Food Loss and Waste country profile for Kenya - Estimates of Food Loss and Waste, associated GHG emissions and nutritional losses - Axmann, Heike; Guo, X.; Kok, M.; Broeze, J.; Víquez Zamora, M.; Soethoudt, J.M. (CGIAR System Organization, 2022)
The UN and the Champions 12.3 Coalition launched the ‘Target-Measure-Act approach’ calling on all governments and companies to set FLW reduction targets, measure FLW, identify hotspots, and to take action to reduce FLW accordingly (Lipinski, 2020). Lack of data makes it particularly difficult for low- and middle-income countries (LMIC) to specify the hotspot food products and chain stages, to define smart targets and to identify adequate interventions. In order to contribute to this essential information we developed and used a mass flow model based on secondary data (see next section for details). This approach allows to present an indicative country profile showing per food product category and chain stage not only the amount of FLW but also the GHGEs related to producing the FLW and induced nutrient losses. This integrated approach towards FLW reduction can support policy makers and other food system actors taking informed decisions contributing to several sustainability objectives in parallel.